Helicobacter pylori: recent advances in the study of its pathogenicity and prevention - Aguilar Germán R.; Ayala Guadalupe; Fierros-Zárate Geny (Instituto Nacional de Salud Pública, 2001)
Helicobacter pylori has acquired great importance during the last two decades, after being recognized as an important pathogen that infects a great portion of the human population. This microorganism is recognized as the main causal agent of chronic gastritis and duodenal ulcers, and it is associated with the subsequent development of gastric carcinoma. The pathogenic mechanisms of H. pylori and their relation to gastric ailments have not been clearly defined. However, at present it is well established that urease, vacuolating cytotoxin VacA, and the pathogenicity island (cag PAI) gene products, are the main factors of virulence of this organism. Thus, individuals infected with strains that express these virulence factors probably develop a severe local inflammation that may induce the development of peptic ulcer and gastric cancer. The way the infection spreads throughout the world suggests the possibility that there are multiple pathways of transmission. Due to the importance that H. pylori has acquired as a human pathogen, laboratories worldwide are attempting to develop a vaccine that confers long-term immunological protection against infection by this microorganism. Hence, the objective of this review is to present the most relevant findings of the biology of H. Pylori and its interaction with the human host. The full version of this paper is available too at: http://www.insp.mx/salud/index.html